1994
DOI: 10.1002/ptr.2650080503
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the flavone luteolin, isolated from Colchicum richii, on guinea‐pig isolated smooth muscle and heart and on blood pressure and blood flow

Abstract: The effects of the flavone luteolin, extracted from Cokhkum richii, on guinea-pig isolated ileum, pulmonary artery, trachea, atrium, perfused heart, and on blood pressure and blood flow of anaesthetized guinea-pigs were studied. Luteolin (10-'-3 X M) caused concentration-dependent relaxation of the tone of ileum, epinephrineprecontracted pulmonary artery and only mild relaxation of acetylcholme-precontracted trachea. These effects were not affected by pretreatment with 1 m M theophylline except in the ileum wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…In some cases, mechanisms underling the antispasmodic activity of tested extracts are also reported (Gilani et al, 2005(Gilani et al, , 2006(Gilani et al, , 2007(Gilani et al, , 2008. Extensive investigations of active antispasmodic extracts have led to the isolation of active compounds belonging to different phytochemical groups (Abdalla et al, 1994;Bergendorff and Sterner, 1995;Rojas et al, 1995Rojas et al, , 1996Trute et al, 1997;Barile et al, 2005).…”
Section: Introductionmentioning
confidence: 93%
“…In some cases, mechanisms underling the antispasmodic activity of tested extracts are also reported (Gilani et al, 2005(Gilani et al, , 2006(Gilani et al, , 2007(Gilani et al, , 2008. Extensive investigations of active antispasmodic extracts have led to the isolation of active compounds belonging to different phytochemical groups (Abdalla et al, 1994;Bergendorff and Sterner, 1995;Rojas et al, 1995Rojas et al, , 1996Trute et al, 1997;Barile et al, 2005).…”
Section: Introductionmentioning
confidence: 93%
“…Currently, it is known that luteolin is effective in terms of antioxidant activation, whitening effect, 44 and repercussive and analgesic actions 45 . In the recent study by Hur, 46 luteolin did not inhibit tyrosinase activation directly, but it concentration-dependently inhibited tyrosinase activation and melanin generation increase by a-MSH in the B16 melanoma cell as well as cAMP generation by MSH and forskolin, which identified the action mechanism of its whitening action generation.…”
Section: Discussionmentioning
confidence: 93%
“…Recently, Fitzpatrick and his collegues (1993) have reported that quercitin (a flavonoid) and tannic acid (tannins) produced endothelium-dependent relaxation in precontracted smooth muscle of intact rat aortic rings. In other respects, flavonoids are also reported for their hypotensive action in anaesthetized guinea-pigs (Abdalla et al, 1994). Regarding the renal effects apparent in 9 week-old rats, Arbutus (250 mg/kg/24 h) induced an important increase of diuresis and natriuresis.…”
Section: Discussionmentioning
confidence: 97%